Influence of laser power and welding speed on dendrite structure growth of low power pulsed laser welded super alloy. Issue 1 (March 2021) - Kumar, Uday; Chattopadhyaya, Somnath; Das, A K; Kumar, Ratnesh; Sharma, Shubham; Nagai, Kaori
Abstract: The influence of different welding parameters like welding speed and laser power on microstructure and the mechanical properties of low power pulsed Nd: Yag laser welded Nickel based super alloy inconel 617 sheets of thickness 1.5 mm has been investigated. In the present study, the welding of the specimens was done in a single pass aimed to full depth penetration. The microstructure of the various samples at fusion zone and at heat affected zone was characterized by field effect scanning electron microscope (FESEM) while the weld size of the welded metal at different parameters were measured using optical microscope (OM). The microhardness in the various zones for the welded sample has also been investigated. The microhardness of the welded samples was compared with base metal after experimental observations. The XRD technique was used to analyze the crystallography of the material at (2θ degree). The material has been used for the present study because of its exceptional properties of heat resistant and corrosion resistant. The Nd: YAG pulsed laser has been used because of its overlapping factor during welding that reduces porosity in the weld zone.